1990
DOI: 10.1258/002367790780890374
|View full text |Cite
|
Sign up to set email alerts
|

Mouse strain differences in resident peritoneal cells: a flow cytometric analysis

Abstract: Summary A f1ow-cytometric study Qfresident peritoneal cells among 8 mouse strains showed a more than twofold variation in the ratio of macro phages to macrophages plus lymphocytes, ranging from 2711/0 in A/J to 62% in C57B/LI0, with significant strain differences in a number of other cellular parameters. There was a particular deficiency of lymphocytes in strain CBA/N, which carries the xid mutation. Studies of the phagocytosis of fluorescent beads also revealed large differences in the number of beads taken u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
3
4
0
Order By: Relevance
“…In contrast, an analysis of total cells in a peritoneal lavage revealed that Balb/c mice contained a large population of small cells (low FSc) with minimal intracellular complexity (low SSc), whereas this population of cells was minimal in C57BL/6 mice (Additional file 1 : Figure S1). These observations confirm the results of Festing et al [ 76 ] that peritoneal cells in Balb/c mice expressed a high ‘lymphocyte’ to ‘macrophage’ ratio whereas the reverse occurs in C57BL strains. Within 24 h after injection of peptide, the population of small cells largely disappeared in Balb/c mice but increased in C57BL/6 mice (Additional file 1 : Figure S1).…”
Section: Resultssupporting
confidence: 92%
“…In contrast, an analysis of total cells in a peritoneal lavage revealed that Balb/c mice contained a large population of small cells (low FSc) with minimal intracellular complexity (low SSc), whereas this population of cells was minimal in C57BL/6 mice (Additional file 1 : Figure S1). These observations confirm the results of Festing et al [ 76 ] that peritoneal cells in Balb/c mice expressed a high ‘lymphocyte’ to ‘macrophage’ ratio whereas the reverse occurs in C57BL strains. Within 24 h after injection of peptide, the population of small cells largely disappeared in Balb/c mice but increased in C57BL/6 mice (Additional file 1 : Figure S1).…”
Section: Resultssupporting
confidence: 92%
“…However, the peritoneum differs from organized lymphoid tissue by having greater numbers of B-1 B cells, fewer T cells, and more macrophages (Hardy 2006; Turchyn et al 2007), factors likely to impact T cell biology both in vivo and in vitro . The strain differences in PerC T cell biology described in this report parallel differences in B-1 B cell and macrophage composition reported among mouse strains (Stadler and de Week 1980; Hayakawa et al 1984; Festing et al 1990; Turchyn et al 2007). The reduced number of B-1B cells and increased macrophage representation in XID mice likely combine to contribute to their distinctive PerC T cell biology.…”
Section: Discussionsupporting
confidence: 77%
“…3D). Lastly, we tested the phagocytic capacity of macrophages by scoring latex bead uptake (28), which was again increased in Mclk1 +/2 cells (Fig. 3E).…”
Section: Increased Classic Activation Of Macrophagesmentioning
confidence: 99%